Echocardiographic evolution and complications in patients with extense anterior myocardial infarction in treatment with warfarin (Boletin Médico de Postgrado, 2022)
A retrospective longitudinal descriptive study was made to determine the echocardiographic evolution of patients with Extensive Anterior Myocardial Infarction (Extensive Anterior MI) under treatment with warfarin who attended the Anticoagulation and Thrombosis Clinic of the Centro Cardiovascular Regional Centro Occidental. The sample consisted of 33 patient records. The age of the patients ranged between 59,64 ± 10,75 years, 60,6% were males; aspirin was the most used anti-platelet drug (21,2%). Baseline LVEF ≤ 40% was associated with a greater presence of IVT (75%), with a gradual reduction up to 6 months. Of the 18 patients with left ventricular thrombus (LVT) in baseline echocardiogram who received anticoagulant treatment, 44,4% maintained the presence of TVI. Of the 15 patients without baseline TVI who received anticoagulant treatment, at 3 months, 26.6% developed TVI.The location of the LVT was mostly apical-septal. Only 12,1% of the patients had an INR in the therapeutic range > 70%. Hemorrhage was the most prevalent complication expressed in ecchymosis/petechiae and epistaxis/gingival bleeding. Ischemic events were not reported.
Keywords: myocardial infarction; echocardiography; warfarin; thrombosis; anticoagulants